PENGARUH PEMBERIAN HORMON 2,4-D DAN BAP TERHADAP PERTUMBUHAN KALUS JERUK KASTURI (Citrus microcarpa) - Imam Mahadi; Wan Syafi'i; Yeni Sari (Biogenesis, 2016)
ABSTRACT The aims of this research to determine the effect of the hormone 2,4-D and BAP on callus growth Kasturi Orange (Citrus microcarpa).  This research consisted of research using experimental method completely randomized design factorial.  Parameters observed is percentage of explants, while appearing callus, callus width and texture of the callus. Research results and a growing percentage of the width callus explants were analyzed by ANOVA and a further test DMRT at 5% level, when it appears callus and callus texture done by descriptively. The result shows that a combination of hormones D4B1 and D4B2 produces a callus emerged fastest of 3.3 HSK. The highest percentage of callus formation that is 100% contained in the treatment of D2B0, D2B0.5 - D4B0. The mean width of callus was highest in treatment D4B2 with a width of 0.97cm. Embryogenic callus resulting by treatment of D2B1, D2B2 ,and D3B0.  Keywords: Hormones, Callus, Orange Kasturi